2004
DOI: 10.1111/j.1442-2042.2003.00763.x
|View full text |Cite
|
Sign up to set email alerts
|

Primary signet ring cell carcinoma of the prostate: Report and review of 42 cases

Abstract: We report a case of primary signet ring cell carcinoma of the prostate in a 75-year-old man. Serum prostate specific antigen (PSA) level at presentation was 9.3 ng/mL. The tumor was confined within the right prostate lobe and the patient was treated with neoadjuvant hormonal therapy and radical prostatectomy. He was alive with no evidence of disease 12 months after surgery. None of the tumor was stained with periodic acid-Schiff and Alcian blue. Immunohistochemically, the tumor was positive for PSA and prostat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
50
0
8

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 7 publications
2
50
0
8
Order By: Relevance
“…1 Signet-ring cell carcinomas can arise in a wide variety of organs, including lung, [2][3][4][5][6] stomach, 7,8 colon, [8][9][10] breast, 8,11,12 urinary bladder, [13][14][15][16][17] pancreas, 18 salivary glands, 19 and prostate. [20][21][22][23][24][25][26][27][28] The signet-ring configuration seen in adenocarcinomas has traditionally been associated with the accumulation of large amounts of intracytoplasmic mucin. It can also occur as a result of the formation of a true intracytoplasmic lumen with displacement of the nucleus toward the periphery of the cell, in which case, special stains for mucin are often negative, as in the case of signet-ring cell carcinomas of the prostate.…”
mentioning
confidence: 99%
“…1 Signet-ring cell carcinomas can arise in a wide variety of organs, including lung, [2][3][4][5][6] stomach, 7,8 colon, [8][9][10] breast, 8,11,12 urinary bladder, [13][14][15][16][17] pancreas, 18 salivary glands, 19 and prostate. [20][21][22][23][24][25][26][27][28] The signet-ring configuration seen in adenocarcinomas has traditionally been associated with the accumulation of large amounts of intracytoplasmic mucin. It can also occur as a result of the formation of a true intracytoplasmic lumen with displacement of the nucleus toward the periphery of the cell, in which case, special stains for mucin are often negative, as in the case of signet-ring cell carcinomas of the prostate.…”
mentioning
confidence: 99%
“…It is difficult to define an optimum treatment strategy for SRCC of the prostate from the existing data, early diagnosis and local treatment of the prostate when there is no evidence of metastatic disease might improve prognosis. Fujita et al [9] reported that, in primary SRCC of the prostate, the survival rate is about 55% at 3 years and decreases to 12% at 5 years. The same study revealed that prognosis is only related to the stage of the disease at diagnosis and more of these patients present with stage IV.…”
Section: Discussionmentioning
confidence: 99%
“…Pri mer TYHK ta nı -sı için tü mö rün %25'in den faz la sı nı taş lı yü zük hüc re le ri nin oluş tur ma sı ge rek li dir. 1,4,7,8 Pri mer TYHK ta nı sı kon ma dan ön ce ben zer mor fo lo ji ye sa hip ta nı lar ekar te edil me li dir. 5 Ayı rı -cı ta nı da yer alan en önem li lez yon se kon der TYHK'dur.…”
Section: Tar Tiş Maunclassified
“…4,7 Ol gu muz da da tran sü ret ral re zek si yon uygu lan mış olup, tü mör hüc re le rin de SMA ve LCA ile bo yan ma gö rül me di.…”
Section: Dna Içeriği Dna Içeriğiunclassified